Multistage production modeling for the cultivation and processing of eels : an industrial case study - Khammonh Sayasing; Pandey, P. C.; Tang, John C.S.; Nagarur, N. N.; The Government of Switzerland (Bangkok : Asian Institute of Technology, 1993)
The present thesis concerns multistage production planning problem of the Matec eels processing factory which will be build in the near future. Anguila Japonica is eels species that this factory chooses as a raw material . In Thailand nowadays , there is no supply , so factory should grow its own eels ; the growing process of Anguila Japonica will last about 210 days , therefore certain number of eels should be imported from over sea . In this thesis , the multistage production model is developed by using goal programming approach . To get the necessary parameters , author developed Integer Linear Programming model to find out number of different culturing tanks . Finally author will setup plant layout for this factory by using computer soft ware in order to have a good layout for new creating factory.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Production planning; Eels